Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Hydrological Changes of the Irtysh River and the Possible Causes - Feng Huang; Ziqiang Xia; Fan Li; Lidan Guo; Fucheng Yang (Water Resources Management, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Tree ring density‐based summer temperature reconstruction for Zajsan Lake area, East Kazakhstan - Feng Chen; Yujiang Yuan; Wenshou Wei; Lily Wang; Shulong Yu; Ruibo Zhang; Ziang Fan; Huaming Shang; Tongwen Zhang; Yang Li (International Journal of Climatology, 2012)
Wood from Siberian larch ( Larix sibirica Ledeb. ) was collected in Hoboksar County, Xinjiang. Mean latewood densities (LWD) were measured by X‐ray densitometry; individual series were first cross‐dated and then combined to form a standard chronology. We developed a warm‐season (June–August) temperature reconstruction of Zajsan Lake area in East Kazakhstan that spans 1600–2002 based on the standard chronology (LWD). The climate/tree‐growth model accounts for 39.1% of the temperature variance from 1901 to 2002 and shows cold phase during the late 1600s early 1700s followed by a warmer period, with cooling again in the late 1700s early 1800s. Several severely cold warm seasons coincide with major volcanic eruptions. Some of the temperature variations also correspond to variations in solar activity. The similarities in trends of the Zajsan chronology (LWD) and the Qinghe chronology (LWD) in Altai Mountain show that there are common large‐scale climatic forcings in Central Asian. The low‐frequency change of temperature reconstruction is correlated positively with Northern Hemisphere temperatures. Copyright © 2011 Royal Meteorological Society

OsPFA-DSP1, a rice protein tyrosine phosphatase, negatively regulates drought stress responses in transgenic tobacco and rice plants - Bing Liu; Jieqiong Fan; Yang Zhang; Peiqiang Mu; Peng Wang; Jianbin Su; Huihuang Lai; Shaowu Li; Dongru Feng; Jinfa Wang; Hongbin Wang (Plant Cell Reports, 2012)

Role of an isoform-specific serine residue in FMN–heme electron transfer in inducible nitric oxide synthase - Wenbing Li; Weihong Fan; Li Chen; Bradley O. Elmore; Mike Piazza; J. Guy Guillemette; Changjian Feng (JBIC Journal of Biological Inorganic Chemistry, 2012)

Regeneration of Clivia miniata and assessment of clonal fidelity of plantlets - Qin-Mei Wang; Feng-Zhan Gao; Xiang Gao; Fan-Yu Zou; Xin Sui; Meng Wang; Yue-Jun Hui; Li Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

QTL mapping for seedling traits in wheat grown under varying concentrations of N, P and K nutrients - Ying Guo; Fan-mei Kong; Yun-feng Xu; Yan Zhao; Xue Liang; Ying-ying Wang; Diao-guo An; Si-shen Li (Theoretical and Applied Genetics, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Important photosynthetic contribution from the non-foliar green organs in cotton at the late growth stage - Yuan-Yuan Hu; Ya-Li Zhang; Hong-Hai Luo; Wei Li; Riichi Oguchi; Da-Yong Fan; Wah Soon Chow; Wang-Feng Zhang (Planta, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)